2021
DOI: 10.1002/iid3.425
|View full text |Cite
|
Sign up to set email alerts
|

Donor Treg expansion by liposomal α‐galactosylceramide modulates Tfh cells and prevents sclerodermatous chronic graft‐versus‐host disease

Abstract: Background and Aim Chronic graft‐versus‐host disease (cGVHD) is a major cause of nonrelapse morbidity and mortality following hematopoietic stem cell transplantation (HSCT). α‐Galactosylceramide (α‐GC) is a synthetic glycolipid that is recognized by the invariant T‐cell receptor of invariant natural killer T (iNKT) cells in a CD1d‐restricted manner. Stimulation of iNKT cells by α‐GC leads to the production of not only immune‐stimulatory cytokines but also immune‐regulatory cytokines followed by regulatory T‐ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In addition, the adoptive transfer of donor iNKT cells ameliorated GVHD by expanding donor Tregs, in turn preserving the GVT effect (115). In addition to the acute GVHD model, our murine study using chronic GVHD models showed that a-GC treatment could ameliorate chronic GVHD symptoms through the early expansion of donor-derived Tregs followed by the suppression of follicular helper T cells and germinal center B cells (116). Based on the data of preclinical models, a phase 2 clinical study evaluated the efficacy of RGI-2001, a novel liposomal formulation of a synthetic derivative of a-GC in patients who underwent HSCT.…”
Section: A-galactosylceramidementioning
confidence: 87%
“…In addition, the adoptive transfer of donor iNKT cells ameliorated GVHD by expanding donor Tregs, in turn preserving the GVT effect (115). In addition to the acute GVHD model, our murine study using chronic GVHD models showed that a-GC treatment could ameliorate chronic GVHD symptoms through the early expansion of donor-derived Tregs followed by the suppression of follicular helper T cells and germinal center B cells (116). Based on the data of preclinical models, a phase 2 clinical study evaluated the efficacy of RGI-2001, a novel liposomal formulation of a synthetic derivative of a-GC in patients who underwent HSCT.…”
Section: A-galactosylceramidementioning
confidence: 87%
“…The important roles of iNKT cells are well appreciated in allogeneic hematopoietic stem cell transplantation (allo-HSCT) and combined bone marrow (BM) and organ transplantation. iNKT cells from recipients, donors, or third-party can reduce the risk of graftversus-host disease (GvHD) while retaining the graft-versusleukemia/lymphoma (GvL) effect (2)(3)(4)(5)(6)(7). Human CD4 -NKT1 cells, CD4 + IL-4-producing iNKT cells, or murine CD4 + NKT2 cells are effective in this respect (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%